Problematising the decision-usefulness of fair values: empirical evidence from UK financial analysts. Issue 4 (7th June 2021) - Georgiou, Omiros; Mantzari, Elisavet; Mundy, Julia
Abstract : In its recently revised conceptual framework, the IASB re-affirms decision-usefulness as the objective of financial reporting, disregarding claims about its lack of coherence. In this paper, we examine how this notion of decision-usefulness works in practice by focusing on the case of fair value measurement. In particular, we explore how decision-usefulness is perceived and experienced by financial analysts when using fair values in their work. We use the frame of 'problematisation', which involves challenging assumptions in existing literature, to formulate our research question and to interpret our findings. Empirical evidence, drawn from interviews with UK financial analysts and comment letters analysts wrote to the IASB, puts into question three key assumptions inherent in the revised conceptual framework. First, fair values are not considered to be unquestionably useful to decision-making; second, this usefulness is found to be contingent on the context of the decision being made; and third, the qualitative characteristics required to achieve decision-usefulness are challenged for their lack of meaning. Analysts' testimonies also challenge taken-for-granted assumptions implicit in academic studies. Assumptions that the decision-usefulness of fair values can be established prior to practice are re-evaluated. We also reflect on the premise that the decision-usefulness of fair values can be challenged on its underlying market-based economic rationales. Overall, our findings contribute to thinking problematically about decision-usefulness which appears to be contingent rather than given by some predetermined ideals as envisaged in accounting conceptual frameworks.